Maria Stuarda - Stefan Zweig; Lorenza Pampaloni (Milano Rusconi, 1983)
Tav.
Stuart, Mary
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018